Positional stability of the periodontal tissues following crown lengthening surgery - Walid Altayeb; Roberto Rossi; Josep Arnabat-Dominguez (Elsevier, 2022)
Objectives: Functional and esthetic crown lengthening surgery (CLS) is one of the most common surgical procedures in periodontal practice. The healing time necessary to achieve stable periodontal tissues, including the supracrestal gingival tissue (SGT) dimensions, biologic width, and gingival margin position following CLS has been investigated, although conflicting results have been reported. The positional stability of the periodontal tissues may be influenced by anatomical factors such as the periodontal phenotype and variability in the biologic width, in addition to factors related to surgical technique such as the ostectomy approach and the postoperative position of the flap margin. In this review, we have attempted to answer a number of research questions related to the recovery time and stability of the periodontal tissues after CLS. Data, sources and study selection: Randomized controlled trials and clinical observational studies with a minimum follow-up of three months to assess the periodontal tissues after CLS were included. In vitro studies, animal studies, and case report were excluded. Searches were performed using PubMed, SCOPUS, Web of Science, and Google Scholar electronic databases for articles published until April 1, 2022. Conclusions: Significant coronal rebound of the gingival margin can occur after CLS. The periodontal phenotype affects both gingival margin rebound and the healing time, while the surgical technique affects the short-term results and procedure-related morbidity. The amount of osseous resection must be determined on the basis of the individual's baseline SGT dimensions. An adequate healing time (≥3 months) after CLS with ostectomy should be respected to achieve stable and predictable results before placement of the permanent restoration. Clinical significance: The positional stability of the gingival margin after crown lengthening surgery is affected by factors related to the periodontal anatomy and surgical technique, and stable and predictable positions can be achieved by allowing an appropriate healing time of at least 3 months.